KAJIAN PENAMBAHAN RUNWAY BANDAR UDARA INTERNASIONAL SENTANI-JAYAPURA - Violetta Merino; Efendy Tambunan; Agnes Sri Mulyani (UKI Press, 2022)
Sentani Jayapura International Airport is the largest and busiest airport in Papua because apart from serving travel routes to and from Papua. This airport is also a hub to serve travel routes to and from the interior or the Central Mountains in Papua. Therefore, this airport serves various sizes of aircraft from small planes to large planes, which causes a high traffic flow of aircraft movements on the runway. This study will examine the addition of a second runway by analyzing aircraft movements in the next 10 years using regression analysis and analyzing runway capacity and then planning the runway geometry using the FAA (Federal Aviation Administration) and SKEP77 (Government Decree on Airport Operation Technical Requirements). ). The results showed that the prediction of aircraft movements in the 5th year reached 35 aircraft movements every hour. This shows that the capacity on the runway is classified as dense (overload). Therefore, it is necessary to add a second runway so that the aircraft movement is more optimal. Based on the results of the KKOP analysis, there is still room for a second runway with a distance between runways of 350 m. The geometric calculation of the second runway based on the type of aircraft served and its geographical location, obtained a length of 3,000 m with a width of 45 m and a runway shoulder of 7.5 m